Numerical simulation of seasonal currents in the Mekong Coastal Area: a case in 2019 - Nguyen, Thanh Duong; Vu, Duy Vinh; Nguyen, Minh Hai (Vietnam Journal of Marine Science and Technology, 2026)
This study, employing the Delft3D numerical model, investigated the Mekong Delta’s seasonal current dynamics by simulating its hydrodynamic regime in 2019. Using Nash-Sutcliffe Efficiency and Root Mean Square Error metrics, the model’s accuracy in replicating measured water levels (cm) and currents at various stations was validated, achieving acceptable simulation results. This allowed for a reliable analysis of the delta’s current patterns. The study revealed that while the overall direction and peak velocity of current remain relatively consistent throughout the year, their spatial distribution undergoes significant shifts, particularly during the transitional periods between seasons. Monthly flow velocities reflect this seasonality, with strong (up to 1 m/s) and consistent northeast-southwest surface flows during the low flow season (minimal stratification), driven by northeasterly winds. Conversely, the flood season exhibits greater regional variability in velocity and direction due to strong freshwater input and fluctuating winds, with surface velocities reaching 1 m/s in the Mekong estuary in October but decreasing sharply with depth (strong stratification), and flow directions shifting dynamically throughout the season.